Distinct clinical phenotypes of congestion in acute heart failure: characteristics, treatment response, and outcomes. (10th September 2020) - Sokolska, Justyna Maria; Sokolski, Mateusz; Zymliński, Robert; Biegus, Jan; Siwołowski, Paweł; Nawrocka‐Millward, Sylwia; Swoboda, Katarzyna; Gajewski, Piotr; Jankowska, Ewa Anita; Banasiak, Waldemar; Ponikowski, Piotr
Abstract: Aims: Patients with acute heart failure (AHF) are included into clinical trials regardless of differences in baseline clinical characteristics. The aim of this study was to assess patients with AHF according to the presence of central and/or peripheral congestion at hospital admission and evaluate treatment response and outcomes in studied phenotypes. Methods and results: We investigated retrospectively 352 patients (mean age: 68 ± 13 years, 77% men) hospitalized due to AHF with the signs of congestion on admission. Patients were divided according to the type of signs of congestion into three groups: A, isolated pulmonary congestion ( n = 52, 15%); B, isolated peripheral congestion ( n = 31, 9%); and C, signs of mixed (peripheral and central) congestion ( n = 269, 76%). Patients from Group A had lower concentration of urea, bilirubin, and gamma‐glutamyl transferase whereas higher level of haematocrit, albumin, and leukocytes on admission. The highest baseline N‐terminal pro‐B‐type natriuretic peptide level (median: 4113 vs. 3634 vs. 6093 pg/mL) and percentage of patients with chronic heart failure (56 vs. 58 vs. 74%; A vs. B. vs. C, respectively, all P < 0.01) were observed in Group C. There were no differences in terms of demographics, co‐morbidities, left ventricular ejection fraction, and applied treatment between studied groups. Patients from Group A had the highest systolic blood pressure on admission (145 ± 37 vs. 122 ± 20 vs. 130 ± 29 mmHg) and the biggest decrease in systolic blood pressure [−22 (−45 to −4) vs. −2 (−13 to 2) vs. −10 (−25 to 0) mmHg] and heart rate [−16 (−35 to −1.5) vs. −1 (−10 to 5) vs. −7 (−20 to 0) b.p.m.] with the lowest weight change [−1.0 (−1.0 to 0) vs. −2.9 (−3.8 to −0.9) vs. −2.0 (−3.0 to −1.0) kg; all P < 0.01] after 48 h of hospitalization. There were differences in short‐term and long‐term outcomes with favourable results in Group A. Group A experienced less frequent in‐hospital heart failure worsening during the first 48 h (4 vs. 23 vs. 7%), had shorter length of hospital stay [6 (5–8) vs. 7 (5–11) vs. 7 (6–11) days], and had lower 1 year all‐cause mortality (12 vs. 28 vs. 29%; all P < 0.05). Presence of peripheral congestion on admission was independent predictor for all‐cause mortality within 1 year [hazard ratio (95% confidence interval): 2.68 (1.06–6.79); P = 0.04]. Conclusions: Patterns of congestion in AHF are associated with differences in clinical characteristics, treatment response, and outcomes. It needs to be considered once planning clinical trials in AHF.